Comparison of the effectiveness between the adapted-double phototherapy versus conventional-single phototherapy - Pracha Nuntnarumit (2018)
Background: Jaundice is very common in neonates during the first few days of life. Severe hyperbilirubinemia is potentially neurotoxic, resulting in bilirubin encephalopathy. Phototherapy has been used widespread and proven to be effective in lowering serum bilirubin. The efficacy of phototherapy depends on the type of light-source, the intensity of light and the area of skin exposed. Double phototherapy with a fiber-optic blanket has been reported to be more effective in reducing bilirubin than conventional phototherapy. However, a fiber-optic blanket or bili-bed is very expensive, thus the authors designed the adapted-double phototherapy by using ordinary fluorescent lamps that are much cheaper and more easily available. Objective: To compare the efficacy and safety of adapted-double phototherapy (DP) using daylight fluorescent lamps to conventional phototherapy (CP) in healthy term infants with hyperbilirubinemia. Design: Prospective randomized controlled trial study. Method: Term infants who met phototherapy criteria were randomized into two groups of phototherapy; the adapted DP placing daylight fluorescent lamps 38 cm above and 32 cm below the crib to produce 9-10 μw/cm2/nm (n=24) versus CP of similar irradiance (n=27). Result: There were no significant differences between the two groups with respect to birth weight, gestational age, hematocrit at enrollment and cause of hyperbilirubinemia. Infants in the DP group had higher bilirubin levels and were slightly older at the time of enrollment than those in the CP group. The bilirubin reduction rate after therapy was significantly greater in the DP compared to CP; 0.22 ± 0.12 mg/dl/h vs 0.14 ± 0.1 mg/dl/h on day 1 of therapy (p=0.02) and 0.16 ± 0.11 mg/ dl/h vs 0.1 + 0.05 mg/dl/h on day 2 (p=0.06). Duration of phototherapy was shorter in DP; 34.9 ± 12.6 h vs 43.7 ± 17.5 h in CP group (p=0.039). No differences in side effects were found between two groups. Conclusion: The adapted-DP using daylight fluorescent lamps in this study has proven to be safe and more effective in reducing bilirubin than CP. It could be an alternative model for intensified phototherapy as it produces a reasonable cost-effectiveness and is easy to apply.